Comparison Effect of Pyrolysis of Eucalyptus Pellita Bark and Empty Fruit Bunches of Oil Palm to Bio-Oil - Asof, Marwan; Arita, Susila; Andalia, Winny (Jurnal Rekayasa Kimia & Lingkungan, 2023)
The use of eucalyptus pelitta (EP) biomass waste and empty fruit bunch of oil palm(EFB) as raw materials for bio-oil is expected to overcome the existing solid waste problems, reduce pollution due to air pollution, and can produce gas and bio-oil which have potential. as new and renewable energy. This study aims to determine the effect of the type of raw material and temperature regulation on the results of pyrolysis products and the characteristics of the resulting bio-oil. The set temperatures used were 300C, 350C, 400C, 450C, and 500C with the raw materials being Eucalyptus pellita (EP) bark biomass and empty fruit bunches of oil palm (EFB). Pyrolysis that occurs with the equipment configuration used a heating rate of 7-14C/minute, where the main reaction of pyrolysis occurs at a temperature of 150C to 270C so that the set temperature does not have a large effect on the yield or characteristics of bio-oil. EP pyrolysis produced an average bio-oil yield of 41.64%, while EFB pyrolysis produced an average bio-oil yield of 46.72%. Bio-oil produced by pyrolysis of EP has a characteristic average value for density of 1.062362 gr/mL, viscosity of 2.1749 cP, and pH 2-3. Meanwhile, bio-oil produced by pyrolysis of EFB has a characteristic average value for density of 1.043146 gr/mL, viscosity of 1.3582 cP, and pH 3-4. EP bio-oil has a composition of C7-C10 carbon, while EFB bio-oil has a composition of C6-C19 carbon.